SISTEM KEAMANAN PARKIR MENGGUNAKAN CAPTURE FOTOBERBASIS JARINGAN PEER TO PEER (Studi Kasus : Sekolah XYZ) - M.TI, Indera (IIB Darmajaya, 2012)
Parking system is a step to development in regulating the motor vehicle traffic at the school, which is hoped to be utilized to easy in controlling parking data at there. The methodology being used is System Development Life Cycle (SDLC)combination with Waterfall model. Observation and library research has done in gathering data. The implementations of Waterfall Model are explained with system analysis, DFD, normalization, database table structure, relation table, and design input and output. Finally, the parking system has been created to support motor vehicle parking at this school. Keywords: Parking system, data, implementation